Two enteric coated microspheres in cystic fibrosis. Issue 6 (June 1990) - Williams, J; MacDonald, A; Weller, P H; Fields, J; Pandov, H
Abstract : In a randomised single blind crossover study in children with cystic fibrosis and pancreatic insufficiency, two enteric coated microsphere preparations of pancreatin were compared on a capsule for capsule basis, by measuring the coefficient of fat absorption, nitrogen excretion, weight change, and symptom scores after four weeks' treatment with each preparation. Thirty nine subjects were randomly allocated to receive Pancrease followed by Creon or vice versa. Each individual subject received the same number of capsules per day in each study period. Data from 27 children (Pancrease/Creon, n = 13 and Creon/Pancrease, n = 14) wer suitable for analysis. Results showed no significant differences between the two preparations in any variable studied. We conclude that there is no significant difference between Pancrease and Creon when compared on a capsule for capsule basis.